Cantrell : a western duo - Flynn, T. T. (Five Star, A part of Gale, Cengage Learning, 2013)
In Strangers Talk or Die, Jeff Parker comes to an agreement with Fat Sam Scoby, agent for the Skeleton Creek Cross-Bone rustling syndicate, to smuggle gold bars across the Mexican border. But once Parker is in Mexico, he arranges for the gold, now disguised, to be shipped to a man named Ed Bellows in an attempt to outsmart Scoby. In Cantrell, Tom Cantrell's attempt to rebuild the ranch he started with partner Steve Rogers culminates in a cattle drive across the Texas plains to the New Mexico Territory. The herd has been victim to persistent looting by Indians, his partner has been murdered, his partner's wife has sold her interest in the ranch to a mysterious lady, and the stolen cattle are ending up in the herd of Matthew Fallon. Someone doesn't want Cantrell to succeed.